Torsion of Testis in an Infant with Unilateral UDT - Mohammad Kazem Moslemi; Mehdi Abedinzadeh; Shabir Al-Mousawi (Case Reports in Medicine)
Torsion of an undescended testis is uncommon. Torsion of a cryptorchid testicle presents a nonspecific symptomatology. Clinical suspicion indicates emergent surgical exploration, irrespective of Doppler ultrasound with its inherent false negative results. Management of the contralateral testis is controversial. We emphasize the need of a complete physical examination of the child who goes to the emergency room with nonspecific symptoms of abdominal pain and ipsilateral empty hemiscrotum to rule out torsion of a cryptorchid testicle. Herein, we report a one-year-old infant with missed torsion of undescended left testis.